Ferroelectric K0.5Na0.5NbO3 catalysts for dye wastewater degradation. Issue 20 (15th October 2021) - Lun, Mengmeng; Zhou, Xunsheng; Hu, Shanshan; Hong, Ying; Wang, Baolong; Yao, Aihua; Li, Wei; Chu, Benli; He, Qinyu; Cheng, Jun; Wang, Yinzhen
Abstract: K0.5 Na0.5 NbO3 (KNN) particles were prepared by a solid–state method. X–ray diffraction, scanning electron microscopy, UV–visible spectrophotometry, and electrochemical impedance spectroscopy were used to study the structure, morphology, and properties of the samples. The obtained KNN is a ferroelectric material with orthorhombic perovskite structure at room temperature. The KNN particles can be used as piezo/photo–bicatalysts for degrading organic pollutants by utilizing vibrational and solar energy; the catalytic activity of the particles can be significantly improved owing to their polarization under an applied electric field. Poled KNN particles show a bicatalytic degradation ratio of rhodamine B (RhB) dye reaching 92% after 60 min. The results indicate that the KNN particles can be applied as attractive ferroelectric catalysts for organic pollutant degradation. Graphical abstract: Image 1